Penerapan Akuntansi Pertanggungjawaban dengan Anggaran Sebagai Pengendalian Biaya pada Badan Pertanahan Nasional Kota Bengkulu - Efenti Gita Torina; Neri Susanti; Nenden Restu Hidayah (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2022)
The results of this study indicate that the Bengkulu City National Land Agency has developed a good organizational structure. This can be seen from the existence of a clear description of the division of authority and responsibility for each level of management and working relationships between sections within the agency. The existence of an organizational structure allows the success of the planning and control program set by the agency. The preparation of the budget at the Bengkulu City National Land Agency aims to determine the amount of funds needed by each section in financing all operational activities to be carried out and as a tool for management in preventing irregularities in the use of funds. The budget is prepared referring to the 5-year budget plan and the 1-year work plan. The Bengkulu City National Land Agency has not separated the controlled and uncontrolled costs sufficiently, because the Bengkulu City National Land Agency has made financing for personnel expenditures and the purchase of goods. The Bengkulu City National Land Agency has made an accountability report in the form of a budget realization report. In the accountability report, it can be seen how big the comparison between the budget and its realization is, and the difference.